Depression treatment preferences of older white and Mexican origin men(,,,) - Johnson, Megan Dwight (2012)
OBJECTIVE: Among older white and Mexican origin male primary care patients, we examined preferences for features of depression care programs that would encourage depressed older men to enter and remain in treatment. METHOD: Sixty-three (45 white, 18 Mexican origin) older men were recruited in six primary care clinics. All had clinical depression in the past year and/or were receiving depression treatment. Participants completed a conjoint analysis preference survey regarding depression treatments, providers and treatment enhancements. RESULTS: The data suggest that white men preferred medication over counseling [odds ratio (OR): 1.64 95% confidence interval (CI): 1.12–2.41], while Mexican origin men preferred counseling (OR: medication over counseling: 0.28, 95% CI: 0.12–0.66). Both white and Mexican origin men preferred treatment that included family involvement (vs. none) (white: OR: 1.60, 95% CI 1.12–2.30; Mexican origin: OR: 3.31 95% CI 1.44–7.62) and treatment for insomnia (vs. treatment for alcohol use) (white: OR: 1.72, 95% CI 1.01–2.91; Mexican origin: OR: 3.93 95% CI 1.35–11.42). White men also preferred treatment by telephone (OR: 1.80, 95% CI 1.12–2.87). CONCLUSIONS: Findings could inform development of patient-centered depression treatment programs for older men and suggest strategies, such as attention to sleep problems, which providers may employ to tailor treatment to preferences of older men.